Urbanization and Environmental Sustainability: Planning Diagnosis of Symbiosis Between Osogbo City and UNESCO World Heritage Site in Osun State, Nigeria - Oyewale Oyeleye; Liora Bigon (Land)
Recently, the only UNESCO river in Nigeria has become polluted, with its color turning dark brown. Osun River serves not only domestic purposes in the city of Osogbo, but also spiritual purposes during the annual Osun Osogbo Festival (OOF). This study examines the physicochemical properties and presence of heavy metals in Osun River, and the air quality at the heritage site before, during, and after the festival. Water samples from Osun River at the UNESCO site were collected before, during, and after the 2024 festival. The water was analyzed at the Department of Environmental Health Sciences of Osun State University, Nigeria, to determine the quantity of heavy metals present in the river. Additionally, an air quality detector was used to assess the quantity of pollutants (CO2, CO, PM2.5, PM10, TVOC, and HCHO) in the air before, during, and after the festival. In Osun River, the quantities of arsenic and copper were within the permissible levels set by the World Health Organization (WHO) for drinking water, while those of lead, chromium, and cadmium were far above the safety standards set by the WHO. The pollution rate of the river was in the order of festival day > before the festival > after the festival. The air quality on the festival day was hazardous to human health, as particulate matter (PM2.5 and PM10) and carbon dioxide were found to be far above the permissible levels set by the WHO. The implications of the findings of this study are discussed, and measures to ensure the future sustainability of this important UNESCO site in the city of Osogbo are recommended.